The modern condition of problems of management of teaching and support staff of the university in the conditions of transformation of educational institutions - Natalia V. Solovova; Albina M. Sanko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article identifies problems of management teaching and support staff of the University in the conditions of transformation of educational institutions of higher education; is determined by the specificity of transformations in institutions of higher education; clarifies the concept of "educational support staff" of the University. Based on the analysis of scientific literature has defined one of the directions of perfection of management of educational support staff of universities, which is a consistent orientation on the quality assurance of educational and research activities. The authors highlighted the ways of implementing modern personnel policy in the University; the necessity of development of strategy of development of scientific and educational potential of all the structural subdivisions of educational organizations.